2017
DOI: 10.1016/j.joa.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum soluble urokinase‐type plasminogen activator receptor and atrial fibrillation

Abstract: BackgroundCirculating soluble urokinase-type plasminogen activator receptor (suPAR), which can reflect immune activation and low-grade inflammation, may be a novel biomarker of cardiovascular disease.MethodsWe investigated the potential association between suPAR and the prevalence of atrial fibrillation (AF) by analyzing patients with either sinus rhythm, paroxysmal atrial fibrillation (PAF), or non-paroxysmal atrial fibrillation (NPAF), which indicates either permanent or persistent AF.ResultsAmong 426 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…After adjustment for CRP and systolic blood pressure, the highest suPAR values remained significantly associated with AF. 9 In our research suPAR alone, or together with CRP, increased the predictive power of traditional risk factors.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…After adjustment for CRP and systolic blood pressure, the highest suPAR values remained significantly associated with AF. 9 In our research suPAR alone, or together with CRP, increased the predictive power of traditional risk factors.…”
Section: Discussionsupporting
confidence: 47%
“…New data indicate the relationship between high suPAR levels and the presence of atrial fibrillation (AF). 9,10 Patients with AF are at an increased risk of developing serious complications, including strokes, heart failure, dementia and early mortality. 11 AF may be present as paroxysmal (self-terminating AF within 7 days), persistent (lasts longer than 7 days) or as long-standing persistent AF (continuous AF for 12 months).…”
Section: Introductionmentioning
confidence: 99%
“…suPAR may be of value for the evaluation of patients with AF, which may be idiopathic but its prevalence is significantly higher in individuals with other manifestations of cardiac disease. Two retrospective studies among patients admitted to cardiology department, published in 2017, showed that suPAR was associated with AF, particularly non-paroxysmal AF (NPAF) [ 37 ], also was associated with low LVEF and elevated BNP, but not with left ventricular hypertrophy [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] Moreover, multiple studies have found increasing suPAR values to be prognostic for adverse events and mortality in patients with confirmed or suspected cardiovascular disease. 6,7,[36][37][38][39] To the extent of the authors' knowledge, only one study has investigated suPAR's prognostic ability in relation to cardiac surgery and demonstrated that increasing preoperative levels of suPAR were associated with higher risk of postoperative complications and 30-day mortality. 20 However, the study exclusively comprised patients with aortic stenosis for aortic valve replacement.…”
Section: Discussionmentioning
confidence: 99%